Takhrij and Syarah Hadith of Agrotechnology: Benefits of Black Cumin - Sopiyani Sopyan; Wahyudin Darmalaksana; Adjat Sudrajat (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with regard to black cumin. This research method is a qualitative type through literature study and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research are that black cumin plants were popular during the time of the Prophet and were known to have many health benefits. The conclusion of this research is that the takhrij and syarah hadith of black cumin plants besides having benefits as immunomodulators in the health sector, black cumin plants also have benefits in the agribusiness sector.